1975
DOI: 10.1136/jnnp.38.11.1127
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive recovery after severe head injury. 2. Wechsler Adult Intelligence Scale during post-traumatic amnesia.

Abstract: SYNOPSIS The Wechsler Adult Intelligence Scale (WAIS) was administered to two matched groups of severely head-injured patients. The first administration was early in the recovery period, when group I was still in post-traumatic amnesia. The WAIS results for this group were significantly lower than those of group II, who were fully conscious. A follow-up at a later stage of recovery found that group I had substantially caught up with group II on the WAIS. At both administrations the WAIS subtest scores were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1976
1976
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Of particular interest is the finding that, in the longer term, IQ levels were indistinguishable on the basis of PTA duration alone, though a trend was apparent for the longer PTA groups to score slightly less well than the shorter PTA groups. This too is consistent with earlier findings (Mandleberg, 1975 (SD= 15.11), and mean PTA duration for the group as a whole was approximately five weeks (range = four days to approximately six months). The majority of the patients had left school at ages 15 or 16 years.…”
Section: Measurement Of Pta Durationsupporting
confidence: 92%
See 2 more Smart Citations
“…Of particular interest is the finding that, in the longer term, IQ levels were indistinguishable on the basis of PTA duration alone, though a trend was apparent for the longer PTA groups to score slightly less well than the shorter PTA groups. This too is consistent with earlier findings (Mandleberg, 1975 (SD= 15.11), and mean PTA duration for the group as a whole was approximately five weeks (range = four days to approximately six months). The majority of the patients had left school at ages 15 or 16 years.…”
Section: Measurement Of Pta Durationsupporting
confidence: 92%
“…Indirect evidence suggesting that in the relatively long term PTA duration may be of little value in predicting cognitive status is seen in the finding of Mandleberg and Brooks (1975) that a group of severely injured patients eventually reached average levels of ability on the Wechsler Adult Intelligence Scale (WAIS). At the same time, Mandleberg (1975) reported that by about 18 months after injury a group of more severely injured patients (mean PTA = 110 days) had essentially 'caught up' cognitively with an otherwise comparable, though less severely injured, group (mean PTA= 19 days). Moreover, preliminary data presented by Bond (1975), though not subjected to statistical analysis, suggested that PTA duration did not appear to affect cognitive level in the longer term.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given previous evidence that PIQ shows greater decrements during the more acute phases of injury (Becker, 1975;Benayoun et al, 1969;Drudge et al, 1984;Mandleberg, 1975;Mandleberg & Brooks, 1975), it is of interest that no effects for time post-onset were found between clusters. One might have predicted that some of the clusters with significantly lower scores on Performance subtests might show less time since injury.…”
Section: Discussionmentioning
confidence: 90%
“…For example, several studies have shown PIQs to be more affected than VIQs soon after head injury (Becker, 1975;Benayoun, Guey, & Baurand, 1969;Drudge, Williams, Kessler, & Gomes, 1984;Mandleberg, 1975;Mandleberg & Brooks, 1975), but greater improvements in PIQs over the first year post injury or even after lead to the disappearance of this Verbal-Performance discrepancy (Drudge et al, 1984;Mandleberg & Brooks, 1975). Klave and Cleeland (1972) found that PIQ was more related to neurologic indices (e.g., hematoma or longer coma) than was VIQ.…”
mentioning
confidence: 96%